Implementasi Nilai-nilai Pendidikan Agama Islam untuk Menanamkan Kecerdasan Spiritual Dalam Mematuhi Peraturan Sekolah - Kartika, Windi Candra; Fauji, Imam (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this study was to determine the attitudes of junior high school students towards the values of Islamic religious education, spiritual intelligence, and compliance with regulations. This study uses a qualitative method with a phenomenological approach involving Islamic Religious Education teachers, counseling teachers, and students. The techniques used are observation, interviews, and documentation. Observation is used to systematically observe and document a symptom or phenomenon that occurs in research subjects. Observation is a data collection method in which researchers make direct observations of schools by paying closer attention to how children behave, regulations that apply, and activities that are carried out. Students' spiritual intelligence will increase and develop by implementing the values of Islamic Religious Education which have been carried out continuously in daily life. Islamic Religious Education Teachers instill spiritual intelligence by aligning Islamic Religious Education values and strategies so that Islamic values can be well instilled so that the intelligence of students in complying with regulations with sanctions from the school runs as a whole.